PENGARUH MOTIVASI, KOMPETENSI, DAN LINGKUNGAN KERJA TERPERSEPSI TERHADAP KINERJA PEGAWAI ( Studi Pada Badan Kepegwaian, Pendidikan dan Pelatihan Kota Semarang ) - Ani Maisaroh, 14.05.51.0014; Yunianto, Askar (Students' Journal of Economic and Management, 2018)
This study aims to analyze the influence of Motivation, Competence, and Work Environment, on Employee Performance at The Agency Staffing, Education and Training of Semarang City. The population in this study is the total number of employees amounted to 100 respondents. The data used are primary data, that is data obtained directly from the source. The technique used for primary data collection is done by means of questionnaires to the respondents. The data collected in the analysis using factor analysis to test the validity of item statement, reliability testing using cronbach alpha, and hypothesis testing using multiple linear regression. Test result obtained that there is a positive and significant influence of work motivation on employee performance, there is a positive and significant influence of work competence on employee performance, there is a positive and significant influence of work perceived work environment on employee performance. Keywords: Motivation, Competence, Perceived Work Environment, and Employee Performance.